Unruly women: The politics of social and sexual control in the old South - Bynum, Victoria E. (Gender & American culture, 1992)
In this richly detailed and imaginatively researched study, Victoria Bynum investigates "unruly" women in central North Carolina before and during the Civil War. Analyzing the complex and interrelated impact of gender, race, class, and region on the lives of black and white women, she shows how their diverse experiences and behavior reflected and influenced the changing social order and political economy of the state and region. Her work expands our knowledge of black and white women by studying them outside the plantation setting.Bynum searched local and state court records, public documents, and manuscript collections to locate and document the lives of these otherwise ordinary, obscure women. Some appeared in court as abused, sometimes abusive, wives, as victims and sometimes perpetrators of violent assaults, or as participants in illicit, interracial relationships. During the Civil War, women frequently were cited for theft, trespassing, or rioting, usually in an effort to gain goods made scarce by war. Some women were charged with harboring evaders or deserters of the Confederacy, an act that reflected their conviction that the Confederacy was destroying them.These politically powerless unruly women threatened to disrupt the underlying social structure of the Old South, which depended upon the services and cooperation of all women. Bynum examines the effects of women's social and sexual behavior on the dominant society and shows the ways in which power flowed between the private and public spheres. Whether wives or unmarried, enslaved or free, women were active agents of the society's ordering and dissolution.
Keywords: 1800-1899; amériques; approches et analyses; civil war; cours; discipline; féminisme matérialiste; his4443; histoire; histoire des femmes*; histoire et politique; intersectionnalité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

Powers of desire the politics of sexuality - Snitow, Ann Barr; Stansell, Christine; Thompson, Sharon (New feminist library, 1983)
This provocative anthology brings together a diverse group of well-known feminist and gay writers, historians, and activists. They are concerned not only with current sexual issues-abortion, pornography, reproductive and gay rights-but they also raise a host of new issues and questions: How, and in what ways, is sexuality political? Is the struggle for sexual freedom a complement to other struggles for liberation, or will it detract from them? Has the sexual revolution diminished or enriched the lives of women?
Keywords: approches et analyses; cours; discipline; histoire; intersectionnalité; justice sociale; lesbianisme; premier cycle; queer; sciences humaines; sexologie; sexualité; soc2014; thématiques; études féministes